Justification on Choosing Screw Pumping Units as Energy Efficient Artificial Lift Technology - D. I. Sidorkin; K. S. Kupavykh (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper analyzes the main techniques and technologies of oil fluid recovery in the context of energy consumption, significantly rising over the latest decade. It is recognized that the number of publications in the area of energy efficiency is growing steadily. Currently Russian oil and gas industry are facing the task of accelerating reduction of energy consumption while preserving, or even increasing, production rates. The task is complicated by the fact that the majority of deposits in Russia either have already entered (primarily, Volga-Ural region) or are now entering (West Siberia) their last stage of exploration, whereas new deposits in East Siberia are only being brought into production. Furthermore, a lot of new deposits, which provide for high recovery rates, are profitable a priori as at the first stage of exploration they do not need any artificial lift due to their free flow production without any oil well pumps. However, there is a significant share of new deposits with low-permeability reservoirs, which require either a system of reservoir pressure maintenance or periodic hydraulic fracturing. At the same time deposits at the late stages of exploration, apart from the use of pump units, systems of reservoir pressure maintenance and hydraulic fracturing, require regular repair and restoration, measures against salt and heavy oil sediments, mechanical impurities, flooding, etc., which all has a negative effect on well profitability. In order to solve these problems, the authors review existing methods and calculate specific energy consumption using various pump systems for hypothetical wells, varying in yield. According to the research results, it has been revealed that from the point of view of energy efficiency, it is desirable to equip low- and low-yield wells with sucker rod progressive cavity pump units, medium-yield ones – with electric progressive cavity pumps driven by permanent magnet motor, medium- and high-yield wells – with electric progressive cavity pumps or electric submersible pumps driven by permanent magnet motor, depending on the characteristics of the pumpedout oil fluid.